A construction clearing house framework for managing construction knowledge and best practice - Ta'a, Azman; Jamaludin, Roslan; Ahmad, Azizah; Mohamed Elias, Ezanee; Abu Bakar, Hanid Suhairi (IOP Publishing, 2020)
This paper discusses a construction clearing house framework to bridge knowledge management gap in the Malaysian construction industry. A clearing house is an agreed upon mechanism for transferring knowledge, which includes a centralized repository of information and resources on a collection of specific topics that are accessible by interested stakeholders. The focus is on resolving the problem of managing domain knowledge of the construction industry in Malaysia, emphasizing on the knowledge management practices through the capturing and transferring of construction knowledge and best practices of the industry players.The knowledge management research framework used is improvised from the previous researchers, while the transfer and sharing of construction best practices is based on the adapted framework also proposed by the previous researchers. This paper briefly described five areas namely knowledge need analysis, knowledge inventory analysis, knowledge flow, knowledge mapping and the knowledge creation in clearing house framework for sharing/transfer of best practices. The construction knowledge and best practices clearing house framework would facilitate the development of a clearing house system in the future, which will enable players in the industry to both contribute and benefit from the resources contained in the clearing house system. This clearing house framework will enable knowledge management of governance inculcate a good environment for practicing conducive knowledge management through knowledge and best practices sharing in the Malaysian construction industry.